2020
DOI: 10.3390/ijerph17145008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Weeks Direct Instruction and Teaching Games for Understanding Programs on Physical Activity and Tactical Behaviour in U-12 Soccer Players

Abstract: The purpose of this study was to compare the effects of 6 weeks direct instruction and teaching games for understanding (TGfU) programs on the decision-making and execution (post-interventions), as well, as on the physical activity (PA) levels during sessions. Thirty under-12 football players participated in this study (age: 10.3 ± 0.45 years) and were randomly assigned to TGfU (n = 15) or direct instruction (n = 15) group. Two sessions/week were implemented. Results revealed that TGfU promoted higher levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A significant effect in the execution variables was present for passes ( d = 1.10), but not for dribbles ( d = 0.45). In the study by Sierra-Ríos et al ( 2020 ), TGFU outperformed the direct instruction group regarding significantly more successful off-the-ball decisions, and executions (2.62 ≤ d ≤ 2.80; 2 of 2 significant), as well as less unsuccessful actions (2.37 ≤ d ≤ 2.48; 2 of 2 significant). Regarding on-the-ball variables, only significantly fewer inefficient technical actions support the greater effectiveness of TGFU ( d = 2.48), but not more efficient technical executions were found.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A significant effect in the execution variables was present for passes ( d = 1.10), but not for dribbles ( d = 0.45). In the study by Sierra-Ríos et al ( 2020 ), TGFU outperformed the direct instruction group regarding significantly more successful off-the-ball decisions, and executions (2.62 ≤ d ≤ 2.80; 2 of 2 significant), as well as less unsuccessful actions (2.37 ≤ d ≤ 2.48; 2 of 2 significant). Regarding on-the-ball variables, only significantly fewer inefficient technical actions support the greater effectiveness of TGFU ( d = 2.48), but not more efficient technical executions were found.…”
Section: Resultsmentioning
confidence: 89%
“…TGFU was investigated in five studies. Two of these compared TGFU with TL, primarily applying technical drill practices supported by direct instructions (Práxedes et al, 2016 ; Sierra-Ríos et al, 2020 ). The further TGFU-studies without CGs only investigated within-group changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an important group of coaches report using the analytical method and traditional teaching, with emphasis on the competitive aspects of the sport [39]. On the other hand, within the selected studies it is observed that the use of active (or alternative) methodologies improves decision-making based on the game's own foundations [32,41,45], which coincides with what was observed by Sánchez et al [44] where the distance between the execution of the fundamentals and the moment of their use (decision making) affects the final result of sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as GBAs promote the predominant use of playing form activities, which have been highlighted to be more conducive to PA than training form activities [16], it has been suggested that this approach may also have a positive effect on players' PA levels [28]. Indeed, emerging evidence has highlighted that during GBA practice sessions, players accumulated signi cantly higher levels of PA than during traditional approach practice sessions [17,29].…”
Section: Introductionmentioning
confidence: 99%